The regulation of sphingosine-1-phosphate 1 receptor signalling and trafficking in astrocytes : implications for Multiple Sclerosis - Healy, Luke M. (Trinity College (Dublin, Ireland). Department of Physiology, 2012)
Multiple Sclerosis (MS) is a chronic, inflammatory and autoimmune disease of the central nervous system (CNS). Fingolimod (FTY720-P) is an immunomodulatory drug recently granted FDA approval for the treatment of remitting relapsing MS. This compound is a pro-drug and an analogue of sphingosine-1-phosphate (S1P), an important lipid mediator that is implicated in a wide range of biological processes. The clinical benefits of FTY720-P have been attributed to its modulation of a group of G- protein coupled receptors (GPCRs) which naturally bind S1P. Internalisation of these S1P receptors by binding of FTY720-P limits entry of autoreactive T-cells into brain tissue.
Keywords: Physiology, Ph.D.; Ph.D. Trinity College Dublin